2019
DOI: 10.3390/ani9070434
|View full text |Cite
|
Sign up to set email alerts
|

Gilt Management for Fertility and Longevity

Abstract: Substantial evidence supports successful management of gilts as an absolutely necessary component of breeding herd management and the pivotal starting point for the future fertility and longevity of the breeding herd. Therefore, gilt management practices from birth have the potential to influence the future reproductive performance of the sow herd. A good gilt management program will address several key components such as birth traits that determine the efficiency of replacement gilt production; effective sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 85 publications
(168 reference statements)
2
63
0
Order By: Relevance
“…Sow lifetime performance can be categorized as the four components of longevity, prolificacy, fertility and lifetime efficiency of sows. Longevity is measured as the number of parity at removal [2][3][4], herd-life days [9,10] or sow life days. Sow life days is the number of days from birth to removal, whereas herd-life days is the number of days from the date that a sow is first-mated as a gilt to the removal date.…”
Section: Components Of Sow Lifetime Performance In Breeding Herdsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sow lifetime performance can be categorized as the four components of longevity, prolificacy, fertility and lifetime efficiency of sows. Longevity is measured as the number of parity at removal [2][3][4], herd-life days [9,10] or sow life days. Sow life days is the number of days from birth to removal, whereas herd-life days is the number of days from the date that a sow is first-mated as a gilt to the removal date.…”
Section: Components Of Sow Lifetime Performance In Breeding Herdsmentioning
confidence: 99%
“…Longevity of sows is commonly measured as the number of parity at removal [2][3][4][5]. In North America, Japan, Sweden and Spain, the mean parity at removal varies between 3.3 and 5.6 [11][12][13][14][15].…”
Section: Sow Longevitymentioning
confidence: 99%
See 1 more Smart Citation
“…This study clearly showed that sows with late AFM were associated with decreased longevity, prolificacy, fertility and reproductive efficiency measurements except for sow life days. However, AFM can be advanced to some degree by a puberty stimulation program for gilts [10,22], although innately fertile sows do tend to have early AFM and high lifetime performance [22]. Additionally, it is recommended that producers record and pay close attention to gilt age at first-estrus, heat-noservice events and AFM [22].…”
Section: Discussionmentioning
confidence: 99%
“…Gilts are the foundation of efficient breeding herd performance (Patterson & Foxcroft, 2019). However, before entering the breeding population, all replacement gilts are only indirectly measured on maternal capacities such as the total number of teat and the number of functional teats (Norsvin, 2014).…”
Section: Introductionmentioning
confidence: 99%